2019
DOI: 10.4103/jips.jips_141_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the effect of plant extract, Thymus vulgaris and commercially available denture cleanser on the flexural strength and surface roughness of denture base resin

Abstract: Aim: This study aims to evaluate and compare the effect of plant extract (thyme essential oil solution) and commercially available denture cleanser on the flexural strength and surface roughness of denture base resin. Settings and Design: Comparative In-vitro study. Chemical denture cleansers play a vital role in maintaining the hygiene and serviceability of the dentures. Bacterial resistance to these chemical agents paved way to plant-extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…These studies had different testing parameters, immersion periods, cleanser concentration, and simulation duration. The increase in R a may be linked to surface degeneration due to the effervescent action of perborate content in denture cleanser [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies had different testing parameters, immersion periods, cleanser concentration, and simulation duration. The increase in R a may be linked to surface degeneration due to the effervescent action of perborate content in denture cleanser [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies [14,15,17,20,23,[26][27][28]30] reported no significant change in surface roughness, while seven studies [16,19,21,22,24,25,29] reported a significant increase in surface roughness after immersion in chemical denture cleansers. An increase in roughness after using alkaline peroxide has been reported in four studies [16,18,19,22]. In addition, Arbeláez et al (2020) [29] re-ported a significant increase in the surface roughness of resin samples immersed in 0.5% sodium hypochlorite.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, an increase in roughness was reported for samples immersed in chlorhexidine (0.2% or 2%) or in acid-based solutions [19]. The increase in roughness caused by natural substances was only reported by Rachmadi et al (2020) [24], compared to studies that also used extracts and essential oils, no significant alteration in the acrylic resin was observed [18,26,28] (Table 1).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations